On the Method of Zadig : Essay #1 from "Science and Hebrew Tradition" - Huxley, Thomas Henry, 1825-1895 (Salt Lake City, UT : Project Gutenberg, 2001)
"On the Method of Zadig" by Thomas Henry Huxley is a philosophical essay drawn from his broader work "Science and Hebrew Tradition," likely written during the late 19th century. This scientific publication explores the nature of knowledge and reasoning through the allegorical character of Zadig, a philosopher from Voltaire's literary creation. Huxley delves into the methods of scientific inquiry, demonstrating how retrospective analysis leads to insights about the past and the underlying principles of nature. In this essay, Huxley recounts the story of Zadig, who, despite never having seen the Queen's spaniel or the King's horse, uses his powers of observation and reasoning to deduce their characteristics. This exploration emphasizes the idea of "retrospective prophecy," wherein knowledge about past events is derived from observable evidence and logical reasoning, paralleling modern scientific methods such as archaeology and paleontology. By connecting Zadig's approach to that of contemporary scientific practices, Huxley advocates for the value of empirical observation, drawing a connection between the philosophical foundations of the past and the rigorous methodologies of science that enable a deeper understanding of the world. (This is an automatically generated summary.)
Release date is 2001-05-01
Produced by D. R. Thompson, and David Widger
Keywords: Science; Evolution; Bible and science; Paleontology